(untitled) (Research, Society and Development, 2024)
Introduction: In 2023, the World Health Assembly organized by the WHO celebrated the milestone of a 50% increase in the global average life expectancy. The impact of this demographic transition in the medical and surgical context is significant, considering the need for greater deliberation related to the increased sensitivity of the elderly to adverse postoperative reactions. Objective: To analyze the impact of using dexmedetomidine medication over midazolam on the postoperative outcome of the elderly patient. Methodology: This is an integrative review of the literature, including 20 articles published between the years of 2018 and 2023 on platforms such as PubMED, Lilacs, BVS, and Google Scholar. The descriptors dexmedetomidine, midazolam, elderly, and postoperative were used, combined with the Boolean operator "AND". Results: Dexmedetomidine was noted for its significant advantages in terms of the number of postoperative delirium cases, psychomotor agitation, respiratory depression, pain, sleep quality, oxygen need, tremors, and residual sedation. It is important to emphasize the protection of cognitive function provided to elderly patients who used it. Conclusion: The administration of dexmedetomidine as intraoperative sedation showed a lower index of postoperative complications in the elderly population when compared to midazolam. However, it is necessary to conduct new studies on the effects of these drugs in isolated contexts, without comparisons with other medications, specifically in the intraoperative and postoperative scenario.